STUDI FAAL PARU DAN KEBIASAAN MEROKOK PADA PEKERJA YANG TERPAPAR DEBU PADA PERUSAHAAN KONSTRUKSI DI SURABAYA - Mardliyatus Sholihah; Abdul Rohim Tualeka (Universitas Airlangga, 2015)
ABSTRACTDust exposure received by workers can affect workers’s pulmonary function and health condition affected by many factors. This observation conducted on construction. The purpose of this research was identify description about pulmonary function and smoking habit at construction workers. Researcher used cross sectional study. The sample of this research was total population of finishing workers as much as 18 workers who doing construction project in Surabaya . Measurement of dust concentration conducted on three poin, by source of the dust, where workers are working and the outmost point. Research used questionnaires, measurement and inspection. The result of pulmonary function showed that six workers had lung function disorder. Pulmonary function measurement at workers used FEV1 and FVC to be the parameter. The result of measurement on point A is 1.6865 mg/m3, on point B is 1.3227 mg/m3 and on point C is 1.0625 mg/m3. Many workers complained that they felt cough in the morning and suffered about eyes irritation. Based on the result of pulmonary function measurement, the conclution is 4 workers had light obstruction and 2 workers had light restriction. Based on measurement, the average of total dust in the project area is 1.3425 mg/m3. Lung function disorder caused by smoking habit. The workers could stop smoking habit and reduce amount.Keywords: pulmonary function, dust, smoking, construction